Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management - Wolfgang Kersten; Christian M. Ringle; Thorsten Blecker (epubli GmbH, 2021)
This volume contains research contributions by an international group of authors addressing innovative and technology-based approaches for supply chain management. They present business models and investment options for enhanced strategic decision making as well as recent approaches for supply chain analytics and risk management. This volume, edited by Wolfgang Kersten, Christian Ringle and Thorsten Blecker, provides valuable insights into artificial intelligence and digital transformation in Supply Chain Management with regard to: - Advanced Manufacturing and Industry 4.0 - Artificial Intelligence and Blockchain - Business Analytics - Innovation and Technology Management - Supply Chain Risk and Security Management
urn:nbn:de:gbv:830-882.0162579; https://econpapers.repec.org/RePEc:zbw:hiclch:249610; https://econpapers.repec.org/RePEc:zbw:hiclch:249611; https://econpapers.repec.org/RePEc:zbw:hiclch:249612; https://econpapers.repec.org/RePEc:zbw:hiclch:249613; https://econpapers.repec.org/RePEc:zbw:hiclch:249614; https://econpapers.repec.org/RePEc:zbw:hiclch:249615; https://econpapers.repec.org/RePEc:zbw:hiclch:249616; https://econpapers.repec.org/RePEc:zbw:hiclch:249617; https://econpapers.repec.org/RePEc:zbw:hiclch:249618; https://econpapers.repec.org/RePEc:zbw:hiclch:249619; https://econpapers.repec.org/RePEc:zbw:hiclch:249620; https://econpapers.repec.org/RePEc:zbw:hiclch:249621; https://econpapers.repec.org/RePEc:zbw:hiclch:249622; https://econpapers.repec.org/RePEc:zbw:hiclch:249623; https://econpapers.repec.org/RePEc:zbw:hiclch:249624; https://econpapers.repec.org/RePEc:zbw:hiclch:249625; https://econpapers.repec.org/RePEc:zbw:hiclch:249626; https://econpapers.repec.org/RePEc:zbw:hiclch:249627; https://econpapers.repec.org/RePEc:zbw:hiclch:249628; https://econpapers.repec.org/RePEc:zbw:hiclch:249629; https://econpapers.repec.org/RePEc:zbw:hiclch:249630; https://econpapers.repec.org/RePEc:zbw:hiclch:249631; https://econpapers.repec.org/RePEc:zbw:hiclch:249632; https://econpapers.repec.org/RePEc:zbw:hiclch:249633; https://econpapers.repec.org/RePEc:zbw:hiclch:249634; https://econpapers.repec.org/RePEc:zbw:hiclch:249635; https://econpapers.repec.org/RePEc:zbw:hiclch:249636; https://econpapers.repec.org/RePEc:zbw:hiclch:249637; https://econpapers.repec.org/RePEc:zbw:hiclch:249638; https://econpapers.repec.org/RePEc:zbw:hiclch:249639; https://econpapers.repec.org/RePEc:zbw:hiclch:249640; https://econpapers.repec.org/RePEc:zbw:hiclch:249641; https://econpapers.repec.org/RePEc:zbw:hiclch:249642; https://econpapers.repec.org/RePEc:zbw:hiclch:249643; https://econpapers.repec.org/RePEc:zbw:hiclch:249644
Keywords: 650; Advanced Manufacturing; Industry 4.0; Artificial Intelligence; Blockchain; Business Analytics; Innovation Management; Technology Management; Supply Chain Risk Management; Security Management